Medicine prescription : e-management for Pusat Kesihatan Pelajar UMP pharmacy - Nurul Ain, Zawawi (2019)
Medicine prescription is a basic thing that is familiar to pharmacy. Based on the problems that occurred after the medicine is handed to the previous patient, the prescription has been handling manually and using handwriting. The prescription written fades away after a long time being stored. This causes the patient do not know the name of the medicine and how to prescribe the medicine. This system is developed to improve the existing system. Medicine Prescription : E-Management (MPEM) for Pusat Kesihatan Pelajar Universiti Malaysia Pahang (PKP UMP) pharmacy has been developed to help pharmacy staff in managing medicine prescription and medicine stock in an effective way in order to solve the problem of patient confusion and reduce the burden on the pharmacy staff in PKP UMP. The objectives of this system is to study how medicine prescription in PKP UMP pharmacy is converted from manual process to a computerized system, to develop a prototype system of medicine prescription in electronic management system in web based and to validate the proposed prototype system in web based. This system consists of login, manage queue, manage patient prescription, manage medicine information and generate report. Rapid Application Development (RAD) is the methodology used to develop this system. RAD consists of four stages, starting with the requirement planning stage, application design stage, rapid construction stage and transition stage. After the development of the system, User Acceptance Test (UAT) is given to client to ensure that all functions meet the requirement without error. UAT ensures the system achieves the objectives and is able to solve problems that occurred before.